2018
DOI: 10.3389/fpsyg.2018.02007
|View full text |Cite
|
Sign up to set email alerts
|

From Growth Mindset to Grit in Chinese Schools: The Mediating Roles of Learning Motivations

Abstract: Growth mindset and grit have attracted much attention in educational research recently. Yet the underlying mechanisms that relate these variables to each other as well as to other variables remain largely unclear. This study investigates the relationships among growth mindset, learning motivations, and grit. We recruited a total of 1,842 students (884 males and 958 females) from third to ninth grade in a Chinese city. Results from the structural equation model analyzing the students’ responses showed that lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 31 publications
10
69
0
2
Order By: Relevance
“…Participants were asked to respond on a 5-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). This inventory has been used among Chinese adolescents and has good reliability and validity [36]. In this study, a confirmatory factor analysis revealed an acceptable fit: χ 2 /df = 4.55, RMSEA = 0.07, AGFI = 0.92, GFI = 0.93, IFI = 0.93, CFI = 0.93; Cronbach's alpha for the subscale in the current study was 0.81.…”
Section: Growth Mindsetsupporting
confidence: 46%
See 3 more Smart Citations
“…Participants were asked to respond on a 5-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). This inventory has been used among Chinese adolescents and has good reliability and validity [36]. In this study, a confirmatory factor analysis revealed an acceptable fit: χ 2 /df = 4.55, RMSEA = 0.07, AGFI = 0.92, GFI = 0.93, IFI = 0.93, CFI = 0.93; Cronbach's alpha for the subscale in the current study was 0.81.…”
Section: Growth Mindsetsupporting
confidence: 46%
“…Individuals with positive traits (e.g., growth mindset) may be more adaptive when facing negative experiences. A possible explanation for this is that growth mindset is an important positive personal trait, which refers to the belief or notion that personal attributes (e.g., personality, strength, and skill) are improvable rather than immutable [33,36]. As a basic point of view for understanding and interpreting our attributes' behaviors [32], mindsets usually determine individual responses to setbacks and adversities to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Self-Determination Theory implies intrinsic and extrinsic motivation, there were researchers who did not mention Ryan and Deci's theory, which is why intrinsic and extrinsic motivation is separate. The next most often used theory was Flow Theory by Mihaly Csikszentmihalyi (Ebrahimzadeh & Alavi, 2016;Zhao et al, 2018;Chang et al, 2018;etc.). Other motivation theories detected in the articles were the four step model for promoting motivation in learning process: Attention, Relevance, Confidence, Satisfaction (ARCS) Model of motivational design by John Keller (Lin et al, 2018;Schumacher & Ifenthaler, 2018;Setiani et al, 2019;Zhang, 2017;etc.…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%